Relation Between Training Load and Recovery-Stress State in High-Performance Swimming - Collette, Robert; Kellmann, Michael; Ferrauti, Alexander; Meyer, Tim; Pfeiffer, Mark (Frontiers in Physiology, 2018)
The aim of this study was to analyze the individual time-delayed linear effect relationship between training load and recovery-stress state with single case time series methods. Session-RPE (sRPE) and Acute:Chronic-Workload-Ratio (ACWR) were used to compare different methods for quantifying the internal training load with regard to their interrelationship with the recovery-stress state. Internal load and recovery-stress state of five highly-trained female swimmers (training frequency 13.6 ± 0.8 sessions per week) were daily documented over 17 weeks. Two different types of sRPE were applied: RPE*duration (sRPEh) and RPE*volume (sRPEkm). Subsequently, we calculated the ratios ACWRh and ACWRkm (sRPE last-week: 4-week exponentially-weighted-moving-average). The recovery-stress state was measured by using the Acute Recovery and Stress Scale (ARSS), consisting of eight scales, [recovery: Physical-Performance-Capability (PPC), Mental-Performance-Capability (MPC), Emotional-Balance (EB), Overall-Recovery (OR), stress: Muscular-Stress (MS), Lack-of-Activation (LA), Negative-Emotional-State (NES), Overall-Stress (OS)]. To examine the relation between training load and recovery-stress state a cross correlation (Rcc) was conducted. A large variation of training load can be observed in the individual week-to-week fluctuations. Rcc individually reaches values above 0.3, especially with sRPEkm as lead variable. Overall, there is a large range with significant differences between the recovery and stress dimensions of the ARSS and between the training load methods, with sRPEkm having the largest span of R = 1.16. High inter-individual differences between the athletes lie in strength and direction of the correlation |0.66| ≤ Rcc ≥ |-0.50|. The time delayed effects (lags 0-7) are highly individual, however, clear patterns can be observed. The ARSS, especially PPC, OR, MS and OS, is a suitable tool for monitoring the acute recovery-stress state in swimmers. MPC, EB, LA and NES are less affected by training induced changes. Comparably high Rcc and Ranges result from the internal load methods, whereby sRPE, especially sRPEkm, shows a stronger relation to recovery-stress state than ACWR. Based on these results and the individual differences in terms of time delay in training response, we recommend for swimming to use session RPE to monitor the internal training load and to use the ARSS, with a focus at the physical and overall-scales, to monitor the recovery-stress state.